Patient- and procedure-related factors in the pathophysiology of perioperative myocardial infarction/injury. (15th April 2022) - Gueckel, Johanna; Puelacher, Christian; Glarner, Noemi; Gualandro, Danielle M.; Strebel, Ivo; Zimmermann, Tobias; Arslani, Ketina; Hidvegi, Reka; Liffert, Marcel; Genini, Alessandro; Marbot, Stella; Schlaepfer, Maria; et al.
Abstract: Background: Perioperative myocardial infarction/injury (PMI) is a frequent, often missed and incompletely understood complication of noncardiac surgery. The aim of this study was to evaluate whether patient- or procedure-related factors are more strongly associated to the development of PMI in patients undergoing repeated noncardiac surgery. Methods: In this prospective observational study, patient- and procedure-related factors were evaluated for contribution to PMI using: 1) logistic regression modelling with PMI as primary endpoint, 2) evaluation of concordance of PMI occurrence in the first and the second noncardiac surgery (surgery 1 and 2). and 3) the correlation of the extent of cardiomyocyte injury quantified by high-sensitivity cardiac troponin T between surgery 1 and 2. The secondary endpoint was all-cause mortality associated with PMI reoccurrence in surgery 2. Results: Among 784 patients undergoing repeated noncardiac surgery (in total 1′923 surgical procedures), 116 patients (14.8%) experienced PMI during surgery 1. Among these, PMI occurred again in surgery 2 in 35/116 (30.2%) patients. However, the vast majority of patients developing PMI during surgery 2 (96/131, 73.3%) had not developed PMI during surgery 1 (phi-coefficient 0.150, p < 0.001). The correlation between the extent of cardiomyocyte injury occurring during surgery 1 and 2 was 0.153. All-cause mortality following a second PMI in surgery 2 was dependent on time since surgery (adjusted hazard ratio 5.6 within 30 days and 2.4 within 360 days). Conclusions: In high-risk patients, procedural factors are more strongly associated with occurrence of PMI than patient factors, but patient factors are also contributors to the occurrence of PMI. Highlights: Perioperative myocardial infarction/injury (PMI) detected by cardiac troponin is a frequent complication of noncardiac surgery. Procedural factors are more strongly associated with occurrence of PMI than patient factors in contrast to spontaneous AMI. Repeated PMI increased 1-year mortality considerably. Mortality was particularly high in the first weeks after surgery.